2022
DOI: 10.1051/0004-6361/202244179
|View full text |Cite
|
Sign up to set email alerts
|

Using the polarization properties of double radio relics to probe the turbulent compression scenario

Abstract: Context. Radio relics are megaparsec-sized synchrotron sources located in the outskirts of some merging galaxy clusters. Binarymerging systems with a favorable orientation may host two almost symmetric relics, named double radio relics. Aims. Double radio relics are seen preferentially edge-on and, thus, constitute a privileged sample for statistical studies. Their polarization and Faraday rotation properties give direct access to the relics' origin and magnetic fields. Methods. In this paper, we present a pol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 111 publications
(176 reference statements)
0
1
0
Order By: Relevance
“…In most cases, radio relics show a high degree of polarisation, whose origin was uncertain for a long time (e.g., [162,175,213,214,[217][218][219] and references therein). The two competing scenarios were that the degree of polarisation is caused either by a magnetic field that is ordered on large scales, or by the compression and alignment of a magnetic field that is tangled on small scales [220].…”
Section: Polarisationmentioning
confidence: 99%
“…In most cases, radio relics show a high degree of polarisation, whose origin was uncertain for a long time (e.g., [162,175,213,214,[217][218][219] and references therein). The two competing scenarios were that the degree of polarisation is caused either by a magnetic field that is ordered on large scales, or by the compression and alignment of a magnetic field that is tangled on small scales [220].…”
Section: Polarisationmentioning
confidence: 99%
“…Knowles et al (2022) reported the detection of a new candidate relic (see Figure 4.1) in the North West direction of the cluster which is smaller and fainter than the previously observed South East relic. The Abell 521 relic pair has a configuration in the North-West South-East direction and has been noted as a double relic system (Stuardi et al, 2022). The Abell 521 South East relic spectral index has been estimated to be −1.45±0.02 between the 153 MHz and 5 GHz frequency range (Macario et al, 2013).…”
Section: Cluster Samplementioning
confidence: 99%